2021
DOI: 10.1002/hed.26807
|View full text |Cite
|
Sign up to set email alerts
|

The role of insurance status as a mediator of racial disparities in oropharyngeal cancer outcomes

Abstract: Background To assess the role of insurance status as a mediator of racial disparities in oropharyngeal cancer outcomes. Methods This was a population‐based retrospective cohort study. Data were extracted from the Surveillance, Epidemiology, and End Results 18 database. The study cohort included 11 627 patients diagnosed with oropharyngeal squamous cell carcinoma between 2010 and 2015. Results The association between black race and increased risk of unresectable disease was slightly attenuated, but persistent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Previous studies have indicated that Black patients are more likely to receive care at low-quality hospitals . This might be an issue of health care access, which is associated with health insurance status, as shown in this study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have indicated that Black patients are more likely to receive care at low-quality hospitals . This might be an issue of health care access, which is associated with health insurance status, as shown in this study.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have indicated that Black patients are more likely to receive care at low-quality hospitals. 37,38 This might be an issue of health care access, which is associated with health insurance status, as shown in this study. We found that Black patients had the highest proportion of being uninsured or having Medicaid, both of which are associated with poorer quality of care.…”
Section: Discussionmentioning
confidence: 63%
“…40 Multiple studies reported that insurance status remained an independent prognostic factor for OS even after accounting for educational attainment, race, disease site, and tumor, node, and metastasis stage of the disease. 7,16,20,40,52,53,[55][56][57][58][59][60][61] Oral Cancer Screenings Oral cancer incidence and mortality were higher among NHB patients and Hispanic patients compared to NHW patients. 3,[62][63][64] Early detection of oral cancer via screening was crucial for reducing mortality rates.…”
Section: Insurance Coveragementioning
confidence: 99%
“…Disparities in insurance coverage are prevalent, with racial/ethnic minorities being more likely to be uninsured or underinsured 36–40 . A recent study on racial and insurance disparities in oropharyngeal cancer demonstrated that insurance status is an important mediator of poor outcomes among Black patients 41 . Black patients were more likely to present with unresectable disease and have worse disease‐specific survival (DSS).…”
Section: Disparities In Otolaryngology–head and Neck Surgerymentioning
confidence: 99%
“…[36][37][38][39][40] A recent study on racial and insurance disparities in oropharyngeal cancer demonstrated that insurance status is an important mediator of poor outcomes among Black patients. 41 Black patients were more likely to present with unresectable disease and have worse disease-specific survival (DSS). Uninsured and Medicaid patients were also more likely to present with unresectable disease and have worse DSS.…”
Section: Disparities In Otolaryngology-head and Neck Surgerymentioning
confidence: 99%